Recreational and ergogenic substance use and substance use disorders in elite athletes: a narrative review - McDuff, D.; Stull, T.; Castaldelli-Maia, J. M.; Hitchcock, M. E.; Hainline, B.; Reardon, C. L. (British Journal of Sports Medicine, 2019)
Background: Substances from various classes may be used for recreational purposes, self-treatment or to boost performance. When substance use shifts from occasional to regular, heavy or hazardous use, positive and negative effects can develop that vary by substance class and athlete. Regular use of recreational or performance enhancing substances can lead to misuse, sanctions or use disorders.